2002
DOI: 10.1007/s00216-002-1319-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a flow-injection analysis (FIA) enzyme sensor for fructosyl amine monitoring

Abstract: An enzyme-sensor system with flow-injection analysis (FIA) has been developed for the detection of fructosyl amine compounds; the sensor utilizes fructosyl amine oxidase isolated from the marine yeast Pichia sp. N1-1 strain. With this FIA system 0.2 to 10 mmol L(-1) fructosyl valine can be determined. The sensor is approximately five times more sensitive to fructosyl valine, a model compound for glycated hemoglobin HbA1c, than to N(epsilon)-fructosyl lysine, a model compound for glycated albumin. This FIA syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…This selectivity for FV differs from that obtained by FAO from the marine yeast Picha sp. N1-1 strain, reported by Ogawa et al 24 The FPOX-CE and FPOX-CET reactors showed the maximum activities for both FV and FVH at pH values around neutrality. Therefore, the FAOX-TE reactor was operated at pH 8.0, while the FPOX-CE and FPOX-CET reactors were operated at pH 7.0 throughout this work.…”
Section: Characteristics Of Immobilized Enzyme Reactorsmentioning
confidence: 64%
See 3 more Smart Citations
“…This selectivity for FV differs from that obtained by FAO from the marine yeast Picha sp. N1-1 strain, reported by Ogawa et al 24 The FPOX-CE and FPOX-CET reactors showed the maximum activities for both FV and FVH at pH values around neutrality. Therefore, the FAOX-TE reactor was operated at pH 8.0, while the FPOX-CE and FPOX-CET reactors were operated at pH 7.0 throughout this work.…”
Section: Characteristics Of Immobilized Enzyme Reactorsmentioning
confidence: 64%
“…Though the characteristics of the FPOX-CET reactor were similar to those of FPOX-CE in the optimum pH and the substrate specificity, the FPOX-CET reactor had a higher thermostability than the FPOX-CE reactor. All of three immobilized enzyme reactors were more stable than the FAO immobilized sensor reported by Ogawa et al 24 When three enzyme reactors were stored at 4˚C in optimum buffer, they retained most of their activities for 90 days. Thus the storage stability was good for three enzyme reactors.…”
Section: Characteristics Of Immobilized Enzyme Reactorsmentioning
confidence: 68%
See 2 more Smart Citations
“…Until recently, most Fru-Val electrochemical sensors have followed the work of Sodes group and employed fructosyl amine oxidase (FAO) [6]; such an approach has allowed the fabrication of an FAO based electrode for Fru-Val sensing that directly detects hydrogen peroxide from the enzyme-catalyzed reaction. Given that enzymes are inherently temperature sensitive and labile, a nonenzymatic electrochemical means of detecting this key marker of disease progression represents a new and significant diagnostic advance.…”
Section: Introductionmentioning
confidence: 99%